Reinterpretasi Wali Adhal oleh Hakim Pengadilan Agama Metro dalam Penetapan Nomor 13/Pdt.P/2025/PA.Mt - Siti Setia Ningsih; Nency Dela Oktora (Al-Mizan (e-Journal), 2026)
This study analyzes the reinterpretation of the obstinate guardian (wali adhal) in the context of legal pluralism, with reference to the Number 13/Pdt.P/2025/PA.Mt at the Metro Religious Court, where his brother, as a guardian, refused to marry his younger sister who was Muslim. The purpose of this study is to formulate a reinterpretation of wali adhal that accommodates the two legal systems within the framework of rechtsvinding (legal discovery). Using empirical legal methods with a qualitative approach through the study of determination documents, in-depth interviews with judges, and customary stakeholders. The results of the study show that the judge reinterpreted wali adhal from a textual-procedural approach to a substantive-teleological approach by operationalizing maqashid al-sharia, hifzh an-nasl (protection of lineage and dignity), and sadd al-dzari’ah (closure of the path of damage). Judges apply rechtsvinding by integrating the principles of non-discrimination and gender equality, establishing guardianship as a legal solutions that protect women’s rights. The judge positioned Islamic law as the primary legal framework, customary law as a cultural consideration, and human rights as a constitutional safeguard in resolving normative conflicts. This research provides a theoretical contribution in the form of an analytical framework of legal pluralism in the jurisprudence of wali adhal, as well as a practical contribution in the form of a foundation for religious courts in handling similar cases in plural areas.